El principio del interés superior del niño - Legerén Molina, Antonio (Revista de Derecho, 2019)
According to the United Nations Convention on the Rights of the Child 1989, the principle of “best interest” must be the “primary consideration” in making decisions concerning every child (cfr. artículo 3 de cdn). States must implement the relevant procedures to determine which decision corresponds in each case to such interest. Similarly, and for children in an environment of armed conflict, unhcr has developed two methods —“best interest assessment” and “best interest determination” (bid)— that can be applied when the procedures designed by the States are not available. These issues are discussed in this article.